PERLINDUNGAN HAK PEMILIK MEREK TERDAFTAR ATAS PRODUK AMDK TERHADAP PELANGGARAN YANG DILAKUKAN OLEH PELAKU USAHA DEPOT AIR MINUM ISI ULANG - MEYNILA KESUMA GINTING (PREMISE LAW JURNAL, 2015)
The current use of water gallon with registered brand belongs to AMDK has raised a problem in the legal domain of Intellectual Property Rights. The brand which is owned and registered by a party should not be used by the other party for the item with the same kind and class, but in practice, the gallon with registered brand is frequently used by the refill drinking water depot. The use of the AQUA brand gallons of drinking water by the refill drinking water depot businessmen can be categorized as trademark violations if the gallons with registered brand are deliberately prepared by the refill drinking water depot businessmen for sale, while the constraints faced by the owner of the registered brand are internal and the external. Of the efforts to prevent the incident of trademark violation were done by providing sustainable and periodical trainings to optimalize the existence of transporter and distributor partners to actively supervise the use of the AQUA brand gallons of drinking water, and to educate the transporter and distributor partners about brand provisions, performing comprehensive efforts with law enforcement officers and other efforts by actively making several approaches to related agencies such as industry and trade services and the refill drinking water depot businessmen. Keywords: Trademark Violation, Registered Brand, Gallon of Drinking Water